Effects of artificial rearing and restricted nutrient intake during the first three weeks of life on later performance and carcass characteristics of pigs - Allee, G.L.; Noll, M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sixty pigs from nine 1itters were allotted, 24 hours after birth, by litter, sex, and birth weight to three treatments: A) sow reared, B) artificially reared and fed milk replacer ad libitum twice daily (artificially reared-unrestricted), and C) artificially reared and restricted to 50% of the nutrient intake of treatment B (artificially reared-restricted). Artificially reared pigs were housed in individual cages during the 20 day treatment period. After 21 days of age, pigs were fed corn-soybean meal diets ad libitum to slaughter at 220 pounds. Average daily gains and pig weights at 21 days differed significantly (P<.0l) different among all treatments.
Keywords: Swine; Artificial rearing; Performance; Carcass characteristics